EVALUASI KINERJA GURU DALAM PEMBELAJARAN DI SD NEGE-RI SUSUKAN 02 MENGGUNAKAN MODEL CHARLOTTE DANIEL-SON - Annisa Urbaningrum; Suhandi Astuti (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
The uneven quality of instruction among educators and limitations in the aspect of post-daily classroom reflection are the background to writing this article. These operational problems trigger inefficiencies in the transfer of basic character values ​​and weak mitigation of student learning obstacles at the end of the teaching period. The main focus of this scientific study is to describe and evaluate the level of achievement of classroom teacher performance based on the framework of the four domains of the Charlotte Danielson model. The steps of this qualitative descriptive evaluative approach are operated through a review of the performance records of six teacher respondents at SD Negeri Susukan 02. The data collection procedure is collected in a structured manner via direct observation sheets, questionnaires, in-depth interviews, and validation of draft document records. Quantitative data empirically reveals the achievement of lesson planning is categorized as very good with a target completion rate of 83.3 percent, classroom environmental management reaching an average of 77.4 percent, instructional implementation reaching 74 percent, and professional responsibility at 83.3 percent. The main conclusion confirms that standardized classroom interaction monitoring using the Danielson instrument has proven highly reliable in detecting pedagogical weaknesses in educators. Schools are recommended to draft training programs for teaching time management and consistently strengthening higher-order thinking skills. ABSTRAK Kualitas instruksional yang belum merata antar-pendidik serta keterbatasan dalam aspek refleksi pascapembelajaran harian di kelas melatarbelakangi penulisan artikel ini. Masalah operasional tersebut memicu inefisiensi transfer nilai-nilai karakter dasar serta lemahnya mitigasi kendala belajar peserta didik pada durasi akhir pengajaran. Fokus utama kajian ilmiah ini adalah mendeskripsikan dan mengevaluasi tingkat ketercapaian kinerja guru kelas berdasarkan kerangka empat domain model Charlotte Danielson. Langkah-langkah pendekatan evaluatif deskriptif kualitatif ini dioperasikan melalui peninjauan rekam kinerja terhadap enam responden guru di SD Negeri Susukan 02. Prosedur pengumpulan data dihimpun secara terstruktur via lembar observasi langsung, kuesioner angket, wawancara mendalam, serta validasi draf rekam dokumen. Data kuantitatif secara empiris menyingkap ketercapaian perencanaan pembelajaran berkategori sangat baik dengan angka ketuntasan target 83,3 persen, tata kelola lingkungan kelas meraih rerata 77,4 persen, pelaksanaan instruksional menyentuh angka 74 persen, serta tanggung jawab profesional sebesar 83,3 persen. Simpulan utama menegaskan bahwa standardisasi monitoring interaksi kelas menggunakan instrumen Danielson terbukti sangat andal dalam mendeteksi kelemahan pedagogik pendidik. Pihak sekolah direkomendasikan menyusun draf program pelatihan manajemen waktu pengajaran dan penguatan keterampilan berpikir tingkat tinggi secara konsisten.